Analysis of Junior High School Students’ Pseudo-Thinking Processes in Solving Problems on Exponential Numbers - Nazila Khairunisa; Mubarik Mubarik; Ibnu Hadjar; Pathuddin Pathuddin (JURNAL PENDIDIKAN MATEMATIKA, 2026)
This study aims to analyze the pseudo-thinking processes of eighth-grade students as they solve problems on the topic of powers. This study employs a qualitative approach using a descriptive research design. The study was conducted at a school in Palu City, with the research subject consisting of one eighth-grade student selected through purposive sampling based on test results. Data were collected through written tests and semi-structured interviews. Data validity was ensured through techniques such as extending the observation period, increasing diligence, and member checks, while data analysis was conducted through the stages of data condensation, data presentation, and drawing conclusions. The results of the study indicate that research subjects were categorized as exhibiting pseudo-correct thinking when they were able to arrive at the correct answer but were unable to provide a conceptual justification for the solution steps they used, as they relied more on their memory of previously learned procedures. The findings of this study indicate the importance of instruction that not only emphasizes procedures but also provides students with opportunities to explain the conceptual reasoning behind them, thereby fostering a deeper understanding of the concepts. Keywords: pseudo-thinking, thought processes, powers of numbers